PENGARUH WAKTU PEMERAMAN TERHADAP SIFAT FISIS DAN MEKANIS TANAH EKSPANSIF STABILISASI KAPUR MODIFIKASI ABU VULKANIK MERAPI - , SITI NURLITA FITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Clay soils have a high plasticity with a high degree of high shrinkage and low strenght. Many examples of damage arising from the nature of the expansive clay soils, such as a decrease in building foundations, crackes and waves on the highway structures, bridge abutments tilt, and others. Many things were done to improve the properties of expansive soils, like soil stabilization. Soil stabilization is a soil mixing with certain materials in order to improve the properties of the original soil. In this study, is used lime modified with Merapi volcano ash to improve the physical and mechanical properties as add material. Clay used in this study from Dusun Krebet, Kulon Progo Yogyakarta with a mixture of volcano ash trim variations of as much as 15%, 20% and 25% and 5% addition of lime for every variation of the dry weight of the soil mixture with curing time for 1, 3, 7 and 14 days. The tests were a test of physical and mechanical properties. The results show that for each variation of the mixture, the curing mixture of soil + volcano ash + limestone is influenced by the time. Shrinkage Limit, Plasticity Index (PI), and the permeability coefficient tends to decrease during 14th day. Meanwhile cohesion values decreased on 3rd day and then rise again with increasing curing aging time, so that the value of increased soil parameters was increased. Based on these results, it can be concluded that the longer the curing aging time on a mixture of clay, the better results will be obtained to improve soil properties.